2021
DOI: 10.3389/fpos.2020.601323
|View full text |Cite
|
Sign up to set email alerts
|

Equity at the Ballot Box: Health as a Resource for Political Participation Among Low-Income Workers in Two United States Cities

Abstract: Objective: The purpose of this study is to identify health resources associated with propensity to vote at the local-level among low-wage workers in two United States. cities. Literature confirms individuals of lower income have a lower propensity of turning out to vote, yet few studies have focused on low-income populations to identify the variation in factors associated with voting within this group. Furthermore, few studies have investigated health and voter turnout at the local-level. In this study, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
(115 reference statements)
0
5
0
Order By: Relevance
“…The Progresa results also have important implications for the mass policy feedback literature that focuses on political participation and government support. The existing mass policy feedback literature establishes that transferred resources can boost the capacity to participate in political and civic activities (Campbell, 2003;McGuire et al, 2021;Mettler, 2002Mettler, , 2005Schober, 2019;Shore, 2014), create incentives to defend the policy (Campbell, 2003;Pierson, 1993), increase the likelihood that organizations will mobilize beneficiaries (Campbell, 2003), and boost political efficacy (Hunter & Sugiyama, 2014;Jacobs et al, 2021). Just as transferred resources create multiple political mechanisms (i.e., political feeds) for beneficiaries to increase political participation and support for the policy providers, transferred resources generate economic mechanisms that affect consumption behavior in the mass public and subsequent policy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The Progresa results also have important implications for the mass policy feedback literature that focuses on political participation and government support. The existing mass policy feedback literature establishes that transferred resources can boost the capacity to participate in political and civic activities (Campbell, 2003;McGuire et al, 2021;Mettler, 2002Mettler, , 2005Schober, 2019;Shore, 2014), create incentives to defend the policy (Campbell, 2003;Pierson, 1993), increase the likelihood that organizations will mobilize beneficiaries (Campbell, 2003), and boost political efficacy (Hunter & Sugiyama, 2014;Jacobs et al, 2021). Just as transferred resources create multiple political mechanisms (i.e., political feeds) for beneficiaries to increase political participation and support for the policy providers, transferred resources generate economic mechanisms that affect consumption behavior in the mass public and subsequent policy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Voting occurs at substantially higher rates, independent of wealth and education, among healthier members of the American electorate ( McGuire et al, 2021 ; Pacheco & Fletcher, 2015 ; Sund, Lahtinen, Wass, Mattila, & Martikainen, 2017 ). Politicians are said to disproportionately respond to the policy preferences of voters compared to non-voters ( Griffin & Newman, 2005 ; Martin, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that different chronic health conditions have varying associations with the likelihood to vote, implicating that some groups are more vulnerable to being underrepresented in politics. The health and voter turnout relationship should be further investigated within specific groups, such as age and income levels, and among those with specific health conditions, to understand the sources of variation to voter turnout within these groups, rather than exclusively examining cross‐group differences as this study did (Hirsch et al, 2019; McGuire et al, 2021). For instance, a recent study including 51 participants in North Carolina found that among those in the study sample living with a traumatic brain injury being married was associated with a lower likelihood of voter turnout, contrary to the typical findings among studies that examine the relationship between marriage and voter turnout in the national population (Hirsch et al, 2019).…”
Section: Discussionmentioning
confidence: 99%